Timed barium esophagography to predict recurrent achalasia after peroral endoscopic myotomy: a retrospective study in Thailand - Tharathorn Suwatthanarak; Chainarong Phalanusitthepa; Chatbadin Thongchuam; Thawatchai Akaraviputh; Vitoon Chinswangwatanakul; Thikhamporn Tawantanakorn; Somchai Leelakusolvong; Monthira Maneerattanaporn; Piyaporn Apisarnthanarak; Jitladda Wasinrat (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Achalasia is a rare esophageal motility disease, for which peroral endoscopic myotomy (POEM) has emerged as a promising treatment option; however, recurrence remains a challenge. Timed barium esophagography (TBE) is a useful diagnostic tool and potential outcome predictor of achalasia. This study aimed to determine predictive tools for recurrence after POEM. Methods This retrospective study enrolled achalasia patients who underwent POEM between January 2015 and December 2021. Patients were categorized into two groups using the 1-month post-POEM Eckardt scores and TBE: the discordant group (Eckardt score improved >50%, TBE decreased <50%) and the concordant group (both Eckardt score and TBE improved >50%). Recurrence was defined as a reincrease in the Eckardt score to more than three during follow-up. Results Complete medical records were available in 30 patients who underwent POEM. Seventeen patients (56.7%) were classified into the discordant group, while 13 patients (43.3%) were in the concordant group. The overall recurrence rate was 11.9% at 1-year, increasing to 23.8% during the extended follow-up. The discordant group had a 6.87 fold higher recurrence rate than the concordant group (52.9% vs. 7.7%, p=0.017). Conclusions These results strongly suggest that combining the Eckardt score with TBE can effectively predict recurrent achalasia after POEM. Patients in the discordant group had an elevated risk.